Student career choice in psychiatry: Findings from 18 UK medical schools. (August 2013) - Halder, Neel; Hadjidemetriou, Christiana; Pearson, Rachel; Farooq, Kitty; Lydall, Gregory J.; Malik, Amit; Bhugra, Dinesh
Abstract Psychiatry recruitment continues to be a problem in the UK and large-scale studies are required to understand the factors surrounding this. A quantitative, cross-sectional online survey, incorporating demographics, career choices, teaching exposure, attitudes to psychiatry and personality factors, was administered to final-year UK medical students. A total of 484 students from 18 medical schools responded (66% women). Sixteen (16%) had chosen psychiatry at medical school entry. By final year, 15 respondents (3%) had decided to pursue a career in psychiatry, while another 78 (17%) were seriously considering it. There was little difference in the quality ratings of lectures and small group teaching between those interested in psychiatry and those not. Experience of 'enrichment activities' (psychiatry special study modules or components, psychiatric research, university psychiatry clubs, and psychiatry electives) were significantly more likely to take up psychiatry. Causality cannot, however, be determined in this study. The study identified several distinct groups of UK students: those deciding on psychiatry before medical school and maintaining that career choice, those deciding on psychiatry during medical school, and those interested in other fields. Addressing psychiatry teaching and exposure may improve recruitment into the speciality.